Effect of context-based instructional approach on students’ science process skills acquisition in environmental concepts - Daniel Melesse; Sissay Menkir; Getahun Yemata; Amera Seifu (Education Inquiry)
The purpose of the study was to determine how students’ acquisition of Integrated Science Process Skills (ISPS) was affected by the integration of a context-based instructional approach (CBIA) with the five stages of the learning cycle (5Es LC). Pre- and post-test assessments were administered using a quasi-experimental design to two groups of ninth-grade students: 46 students in the treatment group who were exposed to CBIA and 48 students in the comparison group who were taught using a conventional instructional strategy (CIA). The assessments focused on environmental topics, and ANCOVA, independent sample t-tests, and paired sample t-tests were used in the data analysis. The science process skill test scores of the treatment group showed a significant favourable effect of CBIA, with no discernible gender-based differences. In conclusion, the study suggested that the integration of CBIA with 5Es LC was more effective than traditional teaching methods in improving students’ ISPS proficiency.